Room-temperature brittle transparent rock-like material and preparation method thereof
By using transparent rock materials with specific ratios of epoxy resin, accelerator and curing agent at room temperature, the problems of rock mass sampling difficulties and low-temperature test environment in the prior art are solved, and the preparation of high brittle and high-transparent materials are realized, which is suitable for studying the crack propagation process of internal rock mass.
Patent Information
- Application Number
- CN202411837006.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-25
AI Technical Summary
When studying the crack propagation process and damage characteristics of the rock mass, the prior art faces the problems of difficulty in sampling rock mass, high cost and low repeatability, and requires low temperature freezing treatment to improve material brittleness, but this increases the difficulty of the test and affects the mechanical properties.
A room-temperature brittle transparent rock material technology is used to mix E50 type epoxy resin, methyl accelerator and polyetheramine curing agent in a specific proportion, and after heating, stirring, vacuuming and casting, a room-temperature brittle transparent rock material sample with built-in three-dimensional cracks is prepared.
It realizes the preparation of high brittle and high transparency materials at room temperature, and the tension ratio is within the real rock range, avoids the limitations of the low-temperature test environment, simplifies the sample production and testing process, and improves the accuracy and efficiency of the research.
Smart Images

Figure CN119684751A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a room temperature brittle transparent rock-like material technology and a room temperature brittle transparent rock-like material sample preparation method with built-in three-dimensional cracks. Background Art
[0002] With the rapid development of economy, engineering projects such as tunnel engineering, foundation pit engineering, water conservancy engineering and mining engineering are becoming more and more complex, often facing complex and changeable rock conditions, so the requirements for rock mechanics are getting higher and higher. However, due to the non-transparency of rock, the current research on rock deformation, damage and internal crack propagation usually uses acoustic emission technology and CT scanning. However, these methods face the problems of difficult rock sampling, high cost and low repeatability, which makes the research methods and means more complicated. Therefore, the use of brittle transparent materials with similar rock mechanical properties can make it easier to study the internal crack propagation process and failure characteristics of rock.
[0003] Dyskin and Wong et al. used organic glass to study the law of three-dimensional crack propagation. Guo Yanshuang used unsaturated resin to cast transparent specimens with built-in cracks, and the tension-compression ratio was 1 / 5 at -50°C. Zhu Weishen prepared a transparent resin material with a tension-compression strength ratio of 1 / 6.6 at -15°C, while the tension-compression ratio of real rocks is 1 / 12-1 / 35. In current research, in order to increase the brittleness of the material, the specimen needs to be frozen and the test environment needs to be kept at a low temperature as much as possible, such as testing in a freezing room, which will increase the difficulty of the test and the temperature change during the test will also affect the mechanical properties. At the same time, the tension-compression ratio used to describe the brittleness of the relevant transparent materials is also somewhat different from the tension-compression ratio of the real rock, which will also affect the accuracy of the transparent material simulating the rock. Therefore, in order to more accurately simulate the mechanical properties of the rock, reduce the influence of the ambient temperature on the material, and remove the limitation of the low-temperature test environment, a room temperature brittle transparent rock-like material technology is needed; and when using organic glass materials as molds for preparing specimens, the specimens are difficult to demold and cannot be reused. In nature, rock masses often contain three-dimensional cracks, which will affect the deformation and failure characteristics of the rock mass and the crack evolution process. Therefore, in order to better study the laws of rock crack propagation, when preparing transparent brittle rock materials containing built-in three-dimensional cracks, it is necessary to locate the built-in three-dimensional cracks more accurately. Summary of the invention
[0004] In order to more accurately simulate the mechanical properties of rocks, reduce the impact of ambient temperature on materials, and remove the limitations of low-temperature test environmental conditions, and to make up for the deficiencies in the prior art, the present invention provides a room-temperature brittle transparent rock-like material sample preparation technology and a room-temperature brittle transparent rock-like material sample preparation method with built-in three-dimensional cracks. The specimens prepared using this preparation technology have the characteristics of high brittleness, high transparency, simple manufacture, easy use, low test environment requirements and a wide range, and obvious crack extension laws.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is:
[0006] A room temperature brittle transparent rock-like material, comprising the following components and mass fractions:
[0007] 100 parts of E50 epoxy resin;
[0008] 4-14 parts of methyl accelerator;
[0009] 9 to 28 parts of polyetheramine curing agent.
[0010] The methyl accelerator is DMP30, whose molecular formula is C 15 H 27 N3O.
[0011] The polyetheramine curing agent is D230, and its molecular formula is NH2(CHCH3CH2O) 2.5 CH2CHCH3NH2.
[0012] The present invention provides a method for preparing a room temperature brittle transparent rock-like material; the method comprises the following steps:
[0013] (1) heating the epoxy resin at 30°C to 50°C for 20 to 30 minutes;
[0014] (2) Mixing the epoxy resin, accelerator and curing agent according to the formula, pouring them into a container, and stirring the mixture with a stirrer at a speed of 400 r / min to 1000 r / min to fully mix the mixture to obtain a transparent mixed liquid;
[0015] (3) Vacuuming: Vacuum the transparent mixed liquid for 20 min to 60 min to remove bubbles;
[0016] (4) Sample casting: Place the mold containing the built-in three-dimensional crack on a horizontal workbench, and use a glass rod to guide the transparent mixed liquid prepared in step (3) into the mold for casting; then let it stand at room temperature for shaping before demoulding, and the production is completed.
[0017] The mold containing the cast built-in three-dimensional crack is placed on a horizontal workbench; the built-in crack is placed at the designed position by adjusting the position of the transverse guide rail and the limit screw, and then the thin wire is fixed on both sides of the mold to achieve the positioning effect. The brittle transparent rock-like material prepared by the present invention has high brittleness at room temperature, and the tension-compression ratio is within the range of the tension-compression ratio of real rocks. It can achieve higher brittleness without low-temperature freezing, which is more in line with the mechanical characteristics of rocks, and the high transparency makes it clearer and more accurate to observe the crack extension law.
[0018] Preparation method of room temperature brittle transparent rock-like material specimen with built-in three-dimensional cracks
[0019] The mold with built-in three-dimensional cracks includes an outer frame, an inner mold, a transverse guide rail, a longitudinal guide rail, a limit screw and a ruler; the transverse guide rail, the longitudinal guide rail, the limit screw and the ruler are symmetrically arranged on both sides of the outer frame; the longitudinal guide rail is fixed on the outer frame, the longitudinal guide rail is made of steel in a groove shape, the longitudinal guide rail is connected to the side of the outer frame, and a slidable limit screw is provided on the longitudinal guide rail, the limit screw is put into the longitudinal guide rail and clamped and fixed to the longitudinal guide rail with a screw; the transverse guide rail is a long strip made of steel, and a hollow groove is provided in the middle, the limit screw is passed through the slot of the transverse guide rail, and the transverse guide rail is fixed to the longitudinal guide rail with a screw; the ruler is a transverse ruler and a vertical ruler, which are respectively installed on the transverse guide rail and the longitudinal guide rail; the limit screw is placed in the track of the longitudinal guide rail and moves up and down along the guide rail; the inner mold adopts a silicone mold and is placed in the outer frame.
[0020] Preferably, the outer frame is made of 2 mm thick steel plate, and has a bottom plate only on the bottom surface, and the other surfaces are only a square frame.
[0021] Preferably, the inner mold is a square box body made of silicone with only an upper opening, the inner mold size is 20mm×20mm×40mm, and the rest of the mold except the opening is sealed and placed in the outer frame.
[0022] Preferably, the transverse scale and the vertical scale are installed on the transverse guide rail and the longitudinal guide rail respectively. According to the scales of the two scales, the longitudinal guide rails on both sides of the outer frame are moved to move the transverse guide rail to the predetermined position, and then the thin wire is passed through the slot of the transverse guide rail, and then the thin wire is tightened and fixed on both sides of the inner mold, and then the built-in three-dimensional crack is connected to the thin wire, so that the built-in three-dimensional crack is placed at the designed position, and three-dimensional crack specimens with different positions, different angles, and different numbers of cracks are produced.
[0023] Preferably, the built-in three-dimensional cracks are made of thin mica sheets, thin metal sheets or thin plastic sheets.
[0024] Place the mold containing the built-in three-dimensional cracks cast on a horizontal workbench; by adjusting the position of the transverse guide rail and the limit screw, place the built-in crack at the designed position, and then fix the fine wire on both sides of the mold to achieve the positioning effect.
[0025] The built-in three-dimensional cracks are made of thin mica sheets, thin metal sheets or thin plastic sheets. The mold of the built-in three-dimensional cracks is a silicone mold.
[0026] According to the scales of the two rulers, the longitudinal guides on both sides of the outer frame are moved to move the transverse guides to the predetermined position, and then multiple thin wires are passed through the slots of the transverse guides, and then the thin wires are tightened and fixed on both sides of the inner mold. Subsequently, the built-in three-dimensional cracks are connected to the thin wires, and the built-in three-dimensional cracks are placed at the designed position to produce three-dimensional crack specimens with different positions, angles, and numbers of cracks.
[0027] The sample prepared in the present invention has a tension-compression ratio at room temperature of 25°C, which is within the range of 1 / 12-1 / 35 of the real rock, and a peak strain of less than 3%, which conforms to the mechanical characteristics of brittle rock. The sample mix ratio and basic mechanical parameters at room temperature of 25°C are as follows:
[0028] Mix ratio E50 mass (parts) Polyetheramine curing agent mass (parts) Mass of methyl accelerator (parts) 1 100 28 14 2 100 22.7 6.8 3 100 9 4
[0029]
[0030] The beneficial effects of the present invention are:
[0031] The brittle transparent rock-like material prepared by the present invention has high brittleness at room temperature (25°C). At room temperature, the tension-compression ratio is within the range of the tension-compression ratio of real rocks. Compared with previous studies, it can achieve higher brittleness without low-temperature freezing, which is more in line with the mechanical characteristics of rocks, and the high transparency makes it clearer and more accurate to observe the crack extension law. The mold and manufacturing process in the present invention make the manufacturing of rock-like materials containing three-dimensional cracks simpler. Compared with the organic glass mold that needs to be drilled in advance and sprayed with a release agent, the mold used in the present invention can directly cast the resin and has a high demoulding success rate. The mold can be reused, and the sample can be tested without curing after demoulding, which shortens the time for making the sample and improves the manufacturing efficiency. The present invention uses E50 epoxy resin, methyl accelerator and polyetheramine curing agent. The three materials are cheap. The sample cast according to the mix ratio provided in the present invention reaches the initial setting stage in 60 minutes, the sample releases heat and reacts mildly, the curing time is shorter, and the test efficiency is higher.
[0032] The samples made using this preparation method have the characteristics of high brittleness, high transparency, simple preparation, easy demoulding and high efficiency at room temperature, which solves the problem that brittle rock samples in the past require a low-temperature test environment, making the test more operational. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 A schematic diagram of a mold that can be manufactured with built-in three-dimensional cracks according to an embodiment of the present invention;
[0034] Figure 2 A top view of a mold capable of producing a built-in three-dimensional crack specimen according to an embodiment of the present invention;
[0035] Figure 3 It is a schematic diagram of the connection between the longitudinal guide rail of the mold, the limit screws and the transverse guide rail in the embodiment;
[0036] Figure 4 Schematic diagram of the transverse guide rail in the embodiment;
[0037] Figure 5 The plexiglass mold and resin sample failed to be demoulded;
[0038] Figure 6 This is the stress-strain curve of the complete sample prepared in the present invention under uniaxial compression;
[0039] Figure 7 This is the failure diagram of the complete sample under uniaxial compression in the present invention;
[0040] Figure 8(a) shows the overall picture of a brittle transparent rock-like material sample with a 45° built-in three-dimensional crack.
[0041] Figure 8(b) is a partial enlarged view of the crack propagation of a brittle transparent rock-like material sample with a 45° built-in three-dimensional crack.
[0042] Fig. 9 CT scan image of a rock sample with internal cracks
[0043] Fig.10 Crack growth diagram of a transparent rock-like material sample with two built-in parallel cracks
[0044] Fig.11 Crack propagation diagram of a transparent rock-like material sample with four built-in parallel cracks
[0045] The components in the figure are described as follows: outer frame 1; inner mold 2; longitudinal guide rail 3; transverse guide rail 4; limit screw 5; transverse scale 6-1; vertical scale 6-2; wrap-shaped wing crack 7; petal-shaped crack 8. DETAILED DESCRIPTION
[0046] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments in this application and the technical features in the embodiments can be combined with each other, and the detailed description in the specific implementation mode should be understood as an explanation of the purpose of this application and should not be regarded as an improper limitation on this application. The orientation terms in the description of this application are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on this application.
[0047] A method for preparing a room temperature brittle transparent rock material sample, wherein the raw materials for preparing the sample include commercially available E50 epoxy resin, a methyl accelerator and a polyetheramine curing agent, the three being mixed according to a mass ratio, with 100 parts of the E50 epoxy resin, 4 to 14 parts of the added methyl accelerator, and 9 to 28 parts of the polyetheramine curing agent; the specific steps of the preparation method are as follows:
[0048] (1) Material weighing: Weigh 22 g of E50 epoxy resin, 1.5 g of DMP30 methyl accelerator and 5 g of D230 polyetheramine curing agent according to the above mass ratio;
[0049] (2) Material treatment: Heat E50 epoxy resin at 50°C for 20 minutes to improve the fluidity of the resin and facilitate the discharge of bubbles;
[0050] (3) Material stirring: E50 epoxy resin, DMP30 methyl accelerator and D230 polyetheramine curing agent were mixed according to the mass ratio and poured into a beaker. The mixture was stirred at a speed of 400 r / min using a stirrer for 1 minute to fully mix the mixture to obtain a transparent mixed liquid;
[0051] (4) Vacuuming: Place the transparent mixed liquid in a vacuum debubbling bucket and draw vacuum for 20 minutes to remove bubbles. The specific vacuuming time can be determined by observing whether bubbles still emerge from the transparent mixed liquid;
[0052] (5) Sample casting: Place the mold containing the built-in three-dimensional crack on a horizontal workbench, and use a glass rod to guide the transparent mixed liquid prepared in step (4) into the mold containing the built-in three-dimensional crack sample to cast it; then let it stand at room temperature for 24 hours before demolding, completing the production and obtaining a finished sample.
[0053] A mold containing built-in three-dimensional cracks such as Figure 1 and Figure 2 As shown, an inner mold 2 is installed inside the outer frame 1, and a fixed longitudinal guide rail 3 is installed on the side frame of the outer frame 1, as shown in FIG. Figure 3As shown, the transverse guide rail 4 and the longitudinal guide rail 3 are connected by the limit screw 5, and the limit screw 5 plays the role of fixing the transverse guide rail 4 along the longitudinal guide rail 3, and a scale is set on the longitudinal guide rail 3 and the transverse guide rail 4. Specifically, the outer frame 1 is made of 2mm thick steel plate, which is a square frame with only a bottom plate on the bottom surface and only frames on the other surfaces; the inner mold 2 is a square box body made of silicone with only an upper opening, and the size of the inner mold 2 is 20mm×20mm×40mm. The rest of the mold is sealed except for the opening and is placed in the outer frame 1; as shown Figure 2 As shown, the same longitudinal guide rails 3, transverse guide rails 4 and limit screws 5 are arranged on both sides of the outer frame, so only one side of the structure is explained below; Figure 3 As shown, the longitudinal guide rail 3 is made of steel and is grooved. The longitudinal guide rail 3 is connected to the side of the outer frame 1 by a metal super glue. A slidable limit screw 5 is provided on the longitudinal guide rail 3. The limit screw 5 can be inserted into the longitudinal guide rail 3 and fixed on the longitudinal guide rail 3 by screws. Figure 3 and Figure 4 As shown, the transverse guide rail 4 is a long strip made of steel with a hollow groove in the middle. The limit screw 5 is passed through the groove of the transverse guide rail 4, and the transverse guide rail 4 is fixed to the longitudinal guide rail 3 by screws; the transverse ruler 6-1 and the vertical ruler 6-2 are respectively installed on the transverse guide rail 4 and the longitudinal guide rail 3. According to the scales of the two rulers, the longitudinal guide rails 3 on both sides of the outer frame 1 are moved to move the transverse guide rail 4 to the predetermined position, and then the thin wire is passed through the groove of the transverse guide rail 4, and then the thin wire is tightened and fixed on both sides of the inner mold 2, and then the built-in three-dimensional crack is connected with the thin wire, so that the built-in three-dimensional crack is placed in the designed position, and three-dimensional crack specimens with different positions, different angles, and different numbers of cracks can be produced.
[0054] The built-in three-dimensional cracks are made of 0.1mm thin mica sheets, and three-dimensional cracks can also be made of materials such as plastic sheets or metal sheets.
[0055] Figure 6 The stress-strain curve of the uniaxial compression test of the sample prepared according to the mixing ratio of the present invention is shown in the figure. The mass of the added methyl accelerator accounts for 4% to 14% of the mass of the E50 epoxy resin, and the mass of the polyetheramine curing agent accounts for 9% to 28%. Figure 6 The stress-strain curves of three mix ratio samples are shown in the table below. The mix ratio in the specific implementation example is mix ratio 2. It can be seen from the figure that the effectiveness of the mix ratio and the simulability of different rock strengths are explained.
[0057] Mix ratio E50 mass (parts) Polyetheramine curing agent mass (parts) Mass of methyl accelerator (parts) 1 100 28 14 2 100 22.7 6.8 3 100 9 4
[0058] Figure 7The splitting failure diagram of a complete brittle transparent rock-like material specimen with built-in three-dimensional cracks under uniaxial compression.
[0059] FIG8( a ) is an overall diagram of crack propagation of a 45° built-in three-dimensional crack under uniaxial compression. FIG8( b ) shows obvious wrapped wing cracks 7 and petal-shaped cracks 8 .
[0060] Fig. 9 This is a CT scan image of a rock-like sample containing built-in cracks. From the image, it can be found that petal-shaped cracks 7 identical to those in the present invention appear on both sides of the preset cracks.
[0061] The sample prepared in the present invention has a tension-compression ratio in the range of 1 / 12-1 / 35 at room temperature 25°C, and a peak strain of less than 3%, which conforms to the mechanical characteristics of brittle rock. The basic mechanical parameters at room temperature 25°C are as follows:
[0062]
[0063] Conventional resin casting uses plexiglass as a casting mold, but a mold release agent needs to be sprayed on the surface of the plexiglass mold to make it easier for the resin sample to be removed from the inside of the plexiglass mold. When the demolding fails, the mold and the sample will stick together, causing the sample production to fail. In the present invention, silicone is finally used as the inner mold after testing and comparison, so that the resin sample and the silicone inner mold can be separated without spraying a mold release agent. Cement mortar is usually used as a material to simulate real rocks in nature. The crack extension diagram of the built-in three-dimensional cracks produced in the present invention under uniaxial compression is compared with the image obtained by Wen Maolin's CT scanning of a rock-like sample with built-in cracks produced by cement mortar casting, as shown in FIG. Fig. 9 As shown, it can be found that similar wing cracks appear at both ends of the prefabricated crack, indicating that the preparation material and manufacturing method of the present invention can better simulate real rocks in nature.
[0064] When it is necessary to make different numbers of built-in cracks, the limit screws can be adjusted on the mold to position the built-in cracks according to the designed built-in crack positions, and the built-in cracks can be connected with thin wires. Fig.10 and Fig.11 The following are the crack growth diagrams of the specimen with two built-in parallel cracks and the crack growth diagram of the specimen with four built-in cracks. Wrap-around wing cracks 7 appear in both growth diagrams. Fig.10 and Fig.11 It can be seen that the mold and the manufacturing method of the present invention can produce three-dimensional crack specimens with different positions, different angles, and different numbers of cracks, and the crack extension characteristics are obvious.
[0065] The technical solutions disclosed and proposed by the present invention can be realized by those skilled in the art by referring to the contents of this article and appropriately changing the conditions, routes and other links. Although the methods and preparation techniques of the present invention have been described through preferred embodiments, relevant technicians can obviously modify or re-combine the methods and technical routes described herein without departing from the content, spirit and scope of the present invention to realize the final preparation technology. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention.
Claims
1. A room temperature brittle transparent rock-like material, characterized in that Includes the following components and mass fractions: 100 parts of E50 epoxy resin; 4-14 parts of methyl accelerator; 9 to 28 parts of polyetheramine curing agent.
2. A method for preparing room temperature brittle transparent rock-like material; characterized in that: The steps include: (1) heating the epoxy resin at 30°C to 50°C for 20 to 30 minutes; (2) Mixing the epoxy resin, accelerator and curing agent according to the formula, pouring them into a container, and stirring the mixture with a stirrer at a speed of 400 r / min to 1000 r / min to fully mix the mixture to obtain a transparent mixed liquid; (3) Vacuuming: Vacuum the transparent mixed liquid for 20 min to 60 min to remove bubbles; (4) Sample casting: Place the mold containing the built-in three-dimensional crack on a horizontal workbench, and use a glass rod to guide the transparent mixed liquid prepared in step (3) into the mold for casting; then let it stand at room temperature for shaping before demoulding, and the production is completed. Preparation method of room temperature brittle transparent rock-like material specimens with built-in three-dimensional cracks.
3. The method according to claim 2, characterized in that: The mold with built-in three-dimensional cracks includes an outer frame, an inner mold, a transverse guide rail, a longitudinal guide rail, a limit screw and a ruler; the transverse guide rail, the longitudinal guide rail, the limit screw and the ruler are symmetrically arranged on both sides of the outer frame; the longitudinal guide rail is fixed on the outer frame, the longitudinal guide rail is made of steel in a groove shape, the longitudinal guide rail is connected to the side of the outer frame, and a slidable limit screw is provided on the longitudinal guide rail, the limit screw is put into the longitudinal guide rail and clamped and fixed to the longitudinal guide rail with a screw; the transverse guide rail is a long strip made of steel, and a hollow groove is provided in the middle, the limit screw is passed through the slot of the transverse guide rail, and the transverse guide rail is fixed to the longitudinal guide rail with a screw; the ruler is a transverse ruler and a vertical ruler, which are respectively installed on the transverse guide rail and the longitudinal guide rail; the limit screw is placed in the track of the longitudinal guide rail and moves up and down along the guide rail; the inner mold adopts a silicone mold and is placed in the outer frame.
4. The method according to claim 3, characterized in that: The outer frame is made of 2mm thick steel plate, and only the bottom surface has a bottom plate, and the other surfaces are a square frame with only frames.
5. The method according to claim 3, characterized in that: The inner mold is a square box body made of silicone with only an upper opening. The inner mold has a size of 20mm×20mm×40mm. The rest of the mold except the opening is sealed and placed in the outer frame.
6. The method according to claim 3, characterized in that: The transverse ruler and vertical ruler are installed on the transverse guide rail and the longitudinal guide rail respectively. According to the scales of the two rulers, the longitudinal guide rails on both sides of the outer frame are moved to move the transverse guide rail to the predetermined position, and then the thin wire is passed through the slot of the transverse guide rail, and then the thin wire is tightened and fixed on both sides of the inner mold, and then the built-in three-dimensional crack is connected to the thin wire, so that the built-in three-dimensional crack is placed at the designed position, and three-dimensional crack specimens with different positions, different angles, and different numbers of cracks are produced.
7. The method according to claim 3, characterized in that: The built-in three-dimensional cracks are made of thin mica sheets, thin metal sheets or thin plastic sheets.
Citation Information
Patent Citations
Composition and method for preparing artificial gem
CN101585958A
Preparation method of high-brittleness transparent rock material test piece
CN103773056A
Engineering rock mass heterogeneous simulation test piece based on rock-like resin material and preparation method and application thereof
CN115340319A
High-transparency rock-like resin test piece manufacturing method and simulation test method
CN115824743A
Manufacturing device, manufacturing method and application of full-transparent concrete sample
CN118310832A